The Value of FujiLAM in the Diagnosis of Tuberculosis: A Systematic Review and Meta-Analysis - Li, Zhenzhen; Tong, Xiang; Liu, Sitong; Yue, Jirong; Fan, Hong (Frontiers in Public Health, 2021)
Background: Timely and accurate diagnosis of tuberculosis (TB) remains a major challenge. Lipoarabinomannan (LAM) is a specific component of the cell envelope of Mycobacterium tuberculosis and is also a potential biomarker for the diagnosis of TB. Recently, the Fujifilm SILVAMP TB LAM test (FujiLAM), as a novel urine lateral flow LAM test, was developed for the diagnosis of TB and is convenient and timely. Because of a difference in the diagnostic value of FujiLAM in the original studies, we conducted a meta-analysis to comprehensively assess the diagnostic value of FujiLAM in TB. Data Sources: We performed a literature search using the PubMed and EMBASE databases and commercial Internet search engines to identify studies. Methods: Searches of databases using relevant terms (“tuberculosis” or “TB”) and (“Fujifilm SILVAMP TB LAM” or “FujiLAM”) were performed. Screening, study reviewing, data extracting and assessing data quality was performed independently by two reviewers. We calculated the pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio. To minimize potential heterogeneity, we performed subgroup analyses. Results: Nine articles were included in the meta-analysis. When using the microbiological reference standard (MRS), the results showed that the sensitivity and specificity of FujiLAM were 0.70 and 0.93, respectively, in adults with TB, while the sensitivity and specificity of FujiLAM in children with TB were 0.51 and 0.87. When using a comprehensive reference standard (CRS), the sensitivity and specificity of FujiLAM in adults with TB were 0.59 and 0.96, respectively, while the results showed that the sensitivity and specificity of FujiLAM in children with TB were 0.27 and 0.86, respectively. Subgroup analysis showed that FujiLAM had higher diagnostic sensitivity in patients with human immunodeficiency virus infection or CD4 cell counts < 200 cells/μL, both in adults and children. Conclusions: This meta-analysis suggests that FujiLAM has a high value in the diagnosis of adults with TB.